IMPLEMENTASI PROJECT BASED LEARNING DALAM PENINGKATAN MOTIVASI BELAJAR PESERTA DIDIK STUDI KASUS: PEMBELAJARAN BATIK JUMPUTAN SDN 3 GETAS KAB.TEMANGGUNG - Atik Kurnia Jayanti; Novitasari, Novitasari; Moh. Rusnoto Susanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The background to the problem in this research is the lack of creativity of students in learning. This research applies the Project Based Learning model in learning as an effort to increase students' creativity. This research aims to measure the effectiveness of the Project Based Learning learning model on student creativity in class 5 jumputan batik making learning material. The data collection method in this research is a mixture of qualitative and quantitative. The subjects in this research were students in grades 5 and 6 of SDN 3 Getas for the 2022/2023 academic year, totaling around 56 students. From the results of data processing before implementing the student activeness model it was 52%, while after implementing the project based learning model it was 89%, so there is an increase of 37% from before. From theoretical studies collected, many studies have proven that Project Based Learning can increase students' creativity. In the research conducted, it can be found that the Project Based Learning method is effective in increasing students' creativity based on the results of data collection.